Effects of stereotactic aspiration on brainstem hemorrhage in a case series - Du, Lei; Wang, Ji-Wei; Li, Cong-Hui; Gao, Bu-Lang (Frontiers in Surgery, 2022)
Purpose Brainstem hemorrhage is usually treated conservatively with medication and has high mortality and morbidity rates. Stereotactic aspiration can directly and microinvasively draw out the hemorrhage within a narrow space in the brainstem, thus promoting quick recovery and potentially saving the life of the patient. This study was conducted to investigate the effect of stereotactic aspiration on patients with brainstem hemorrhage in a case series. Materials and methods A total of 42 patients with brainstem hemorrhage were enrolled for stereotactic aspiration of the brain hemorrhage, and another 30 patients with brainstem hemorrhage were enrolled for conservative treatment. The clinical and imaging data were analyzed and compared. Results Stereotactic aspiration was successful in all patients (100%), with immediate elimination of hematoma in the brainstem. In five patients with the hemorrhage extending to the fourth ventricle (n = 1) and basal ganglia (n = 4), the hemorrhage was eliminated, resulting in good outcomes. However, four patients died of multiple organ failure after aspiration, resulting in a mortality rate of 9.5%. One week after surgery, the Glasgow Coma Scale (GCS) score ranged from 3 to 11 (mean 5.9 ± 2.3). At 1-month follow-up, 4 patients died, and 36 patients survived, with the GCS score ranging between 3 and 15 (mean 8.6 ± 2.1), which was significantly (P < 0.01) higher than that before surgery. The Modified Rankin Scale (mRS) score was 5 before treatment, 5 (4.4, 6) at 1 week after surgery, and 5 (4, 6) at 1 month. In the conservative group, 16 (53.3%) patients died during hospitalization. The GCS score was 0–6 (mean 2.3 ± 1.1), which was significantly (P < 0.05) worse than at admission or of that in the aspiration group at 1 month. The mRS score at 1 month was 6 (5, 6), which was significantly (P < 0.05) worse than that in the aspiration group. Conclusion Stereotactic aspiration for brainstem hemorrhage as an approach of microinvasiveness may be effective in evacuating brainstem hemorrhage and may promote quick recovery of the patient, resulting in better clinical outcomes.